EFFECTS OF SUPPLIER DEVELOPMENT PRACTICES ON PERFORMANCE OF PHARMACEUTICAL SUPPLIERS FOR HOSPITALS IN NAIROBI CITY COUNTY - Musyoki, Kiminza B.; Ngugi, Edith (International Journal of Supply Chain Management, 2017)
Purpose: The purpose of this study was to determine the effects of supplier development practices on performance of pharmaceutical suppliers for hospitals in Nairobi City County, Kenya. Methodology: The study employed descriptive research design. The target population for the study was all the pharmaceutical suppliers in Nairobi City County, which were 243. The sample size for the study was 93 pharmaceutical distributors for Nairobi County private and public hospitals. Primary data was collected through a questionnaire. Descriptive and inferential analysis was conducted to analyze the data. The data was presented using tables, graphs and charts. Results: The findings revealed a positive and significant relationship between supplier training, information sharing, management support, strategic partnership and performance of pharmaceutical suppliers for hospitals in Nairobi City County. Unique contribution to theory, practice and policy: Based on the findings, the study recommended that both pharmaceutical distributors and hospitals should invest resources in training pharmaceutical suppliers; there should be better cooperation between the hospitals and pharmaceutical suppliers; both the hospitals and the pharmaceutical suppliers' management should establish a good working relationship; and the government should provide strategic support to the pharmaceutical suppliers. Finally, the study recommended that similar studies should be conducted in other Counties for comparison purposes.